Characteristics Associated With Self-Reported Worry Among Adults About Food Availability and Food Safety During the COVID-19 Pandemic—United States, June 2020 Survey Data. Issue 1 (January 2022) - Dumas, Brianna L.; Lee, Seung Hee; Harris, Diane M.; Yaroch, Amy L.; Pomeroy, Mary A.; Blanck, Heidi M.
Purpose: During a pandemic, persons might experience worry because of threats (real or perceived), or as part of stress-related reactions. We aimed to provide insight into Americans' worry about food during COVID-19.Design, Subjects, Measures: Online survey data from June 2020 (n = 4, 053 U.S. adults; 62.7% response rate) was used to assess 2 outcomes: worry about food availability (FA); food safety (FS). Adults with missing information about FA and FS were excluded from analysis (final n = 3, 652). Analysis: We used descriptive statistics and multivariable logistic regression to examine characteristics associated with the outcomes and estimate adjusted odds ratios (aOR) and 95% confidence intervals (95%CI) for associations between sociodemographic variables and outcomes. Results: 58.3% of respondents reported worry about FA; 57.5% about FS, with higher odds of worry for FA and FS (versus referents) in lower income households (FA: aOR = 1.76 95%CI [1.30, 2.39]; FS: 1.84[1.35, 2.51]); unemployed (1.54[1.05, 2.28]; 1.90[1.26, 2.81]); non-Hispanic Black (1.55[1.14, 2.12]); 2.25[1.65, 3.07]); Hispanic (1.39[1.06, 1.82]; 1.94[1.46, 2.56]). Conclusion: Findings highlight the importance of strategies to reduce consumer worry about FA and FS and negative food behaviors, and the need for continued access to hunger safety net programs, which could have positive effects on nutrition security.